Ambidextrous Leadership and Employee Work Outcomes: A Paradox Theory Perspective - Guo, Zhuopin; Yan, Jiaqi; Wang, Xiaoying; Zhen, Jie (Frontiers in Psychology, 2020)
Numerous studies have examined the influence of ambidextrous leadership on employee work outcomes, but few have explored the issue through the congruence or incongruence of two seemingly conflicting leadership styles. On the basis of paradox theory, we adopted polynomial regression and surface analysis method to investigate the congruent/incongruent effect of loose leadership and tight leadership. We also used a two-wave design with a two-month time interval to reduce the common method bias. By using two-wave surveys of 301 employees, this study posited that ambidextrous leadership congruence leads to higher leader–member exchange quality than incongruence. Loose leadership and tight leadership with high strength play a more positive role in enhancing LMX quality than low strength. This study also demonstrated that LMX quality mediates the relationship between ambidextrous leadership congruence/incongruence and employee work outcomes (i.e. job performance and creativity).